2011
DOI: 10.1103/physrevlett.107.207201
|View full text |Cite
|
Sign up to set email alerts
|

Ab InitioInvestigation of the Elliott-Yafet Electron-Phonon Mechanism in Laser-Induced Ultrafast Demagnetization

Abstract: The spin-flip (SF) Eliashberg function is calculated from first principles for ferromagnetic Ni to accurately establish the contribution of Elliott-Yafet electron-phonon SF scattering to Ni's femtosecond laser-driven demagnetization. This is used to compute the SF probability and demagnetization rate for laser-created thermalized as well as nonequilibrium electron distributions. Increased SF probabilities are found for thermalized electrons, but the induced demagnetization rate is extremely small. A larger dem… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
161
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 171 publications
(168 citation statements)
references
References 22 publications
7
161
0
Order By: Relevance
“…Several competing processes have been proposed for magnetization dynamics on ultrafast timescales [5][6][7][8][9][10][11][12][13] . For the trilayer systems explored here, we find that the observed magnetization dynamics in the Ni and buried Fe layer is consistent with superdiffusion of Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several competing processes have been proposed for magnetization dynamics on ultrafast timescales [5][6][7][8][9][10][11][12][13] . For the trilayer systems explored here, we find that the observed magnetization dynamics in the Ni and buried Fe layer is consistent with superdiffusion of Fig.…”
Section: Discussionmentioning
confidence: 99%
“…A number of distinct models have been proposed to describe how laser excitation can couple so quickly to the spins, given that the light itself does not directly exert a significant torque on the electron spins. Most of these models are based on phonon-, electronand magnon-mediated spin-flip processes [5][6][7][8][9] , direct laser-induced spin-flips 10 or relativistic spin-light interaction 11 . Most recently, a new model based on superdiffusive spin transport has been proposed 12,13 .…”
mentioning
confidence: 99%
“…One way to connect the electron excitation with the spin system has been described by Elliott. [91][92][93] While the spin-flip arising specifically from electronphonon scattering was discussed in the spin relaxation paramagnetic metals by Yafet and called Elliott-Yafet scattering later, 94 in the original work by Elliott the spin-mixing is described much more general, yielding some confusion in the community. Conduction electron spin resonance (CESR) is very important to understand the spin relaxation of the electrons in metals.…”
Section: Theoretical Perspectivesmentioning
confidence: 99%
“…Thus, we have all the ingredients to calculate the initial spin current based on equation (6). If the thickness d of the ferromagnet is smaller than the penetration length of the pump light, we can approximate equation (6) …”
Section: Thermally Induced Spin Currentmentioning
confidence: 99%
“…The first approach is based on spin flips taking place in the bulk of the ferromagnetic material [2][3][4][5][6][7][8][9][10][11][12][13] where in particular Mueller et al [14] identified the chemical potentials for minority and majority electrons as the driving force for spin flips. The second approach describes the demagnetization as a transport effect, where a spin current transports the angular momentum away from the sample surface.…”
Section: Introductionmentioning
confidence: 99%